Adversarial Framing: President Bashar al-Assad’s Depiction of the Armed Syrian Opposition - Fabien Merz (Journal of Terrorism Research, 2014)
'This paper evaluates how Syrian president Bashar al-Assad is framing his opponents in the context of the Syrian civil war. The question is addressed by conducting a qualitative thematic analysis of 13 interviews he gave to international television news networks and newspapers between March and November 2013. It is found that Al-Assad consequently labels the armed opposition as “terrorists” preponderantly composed of groups affiliated to Al-Qaeda. The “terrorists” are framed as posing a threat to the region as well as to international security on a global scale. Furthermore, Al-Assad denies the armed opposition its Syrian grassroots by portraying them as outside aggressors fighting for foreign interests. They are also depicted as “enemies of the Syrian people”, responsible for all the atrocities and human suffering committed during the Syrian civil war.' ' '